ANALYSIS OF THE EFFECT OF SUPERVISORY CONSULTANT PERFORMANCE FACTORS ON THE CONSTRUCTION OF THE TRANS STUDIO BUILDING SURABAYA - Rahman, Medio Duddian Wahyu; Oetomo, Wateno; Nugroho, Laksono Djoko (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
This study aims to determine impact of Understanding Contract Documents, Understanding of Technical Specifications, Use of Materials, Use of Labor, and Use of Equipment on the performance of supervisory consultants. This research conducted with a quantitative method. The sources of data using primary data from interviews. The research population is 70 Consultants for the Construction Project of the Trans Studi Surabaya Building with the sample being the entire population. The data analysis technique using PLS program. The results found that understanding of contract documents and technical specifications has a positive significant impact on the performance of the Supervisory Consultant. Meanwhile, the use of materials, labor and equipment has a positive significant impact on the performance of the Supervisory Consultant.